Peningkatan Kompetensi Pembina Pramuka di Kwartir Ranting Pakal dan Benowo Kota Surabaya Melalui Pembenahan Metode Pelatihan Orang Dewasa - Didik Daryanto; Dwi Prihantono; Yurilla Endah Mulatie (Asian Journal of Innovation and Entrepreneurship, 2019)
Partners in this program are Scoutmaster in District Council Pakal and District Council Benowo, Regency Council of Surabaya City. The problems that occur in this case are the Regency Council Pakal and Benowo is in the preparation of quality Scout coaches that have not been planned well and are used incidentally, the coach's quantity is very lacking, the curriculum in basic proficient courses (KMD) and advanced proficient courses (KML) does not always develop and has not allocated all components in education based on experience, Scout formal advisory education has graduated from high school, there are still many coaches who do not have KMD, a summary about the meaning of educating, not being able to be a good example in the application of education, the ability of coaches to make advanced training, coaches turning into teaching, evaluation and training assessment to administrative and mass, implementing exercises lacking monotonous variation and practice, lack of innovation and creativity in fostering and there are still many coaches who do not understand the Scouting Techniques and Among System . Another method; Workshop, Orientation, Courses, Counseling and Training. The results of this program have been carried out activities which are divided into several stages, namely pre-activity activities, implementation activities and monitoring and evaluation. In the pre-activity phase, it has carried out activities with District Council of Pakal and District Council of Benowo, Coordination with the Mainstay of Provincial Council in East Java, Coordination with Regional Council of Surabaya City, Coordination with sub-districts, schools, speakers, etc. others. During the implementation phase, several activities have been carried out, including; Karang Pamitran (Scoutmaster meeting) was held in several sessions, including: Student Psychology Material, First Aid for Accidents, Hypno teaching for Scoutmasters and Ropes Access. Several activities will be carried out, among others: basic proficient courses (KMD) Advanced Courses and Organizing Cub Jamboree as a activity after KMD.